Bauran Pemasaran dan Kualitas Layanan Kunjungan Terhadap Keputusan Pembelian di Perumahan Greenland: The Mark Eting Mix and The Quality of Visiting Services on Purchasing Decisions at Greenland Residences - Khoirul Marzuki; Tony Irawan; Hartoyo (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: One of the most important needs of today's population is housing. The increase in population has led to an increase in the supply of property, but the demand for property in Bogor Regency has actually decreased. This affects housing sales at Greenland Forest Hill and Greenland Kemang. The variables that influence purchasing decisions are marketing mix and service quality. Purpose: The research objectives are to identify consumer characteristics, analyze the effect of marketing mix and visit service quality, and formulate managerial implications for the company. Design/methodology/approach: The method of data processing and analysis in this study uses descriptive analysis and Structural Equatin Modeling - Partial Least Square (SEM-PLS) analysis by utilizing SmartPLS tools. Findings/Result: The results of the study were 200 respondents in this study with a percentage of Greenland Kemang of 51% and Greenland Forest Hill of 49%.Conclusion: The conclusion of this study is that consumer decisions in Greenland housing are positively and significantly influenced by the variables of purchase intention and behavioral control. This shows that family plays a very big role in deciding to buy a house in Greenland Forest Hill and Kemang. In addition, location indicators and special services for consumers have a more significant influence on purchasing decisions than other variables.Originality/value (State of the art): This research enhances the literature on factors that influence home purchases. This research also shows that marketing mix and service quality can influence purchasing decisions through the theory of planned behavior model. Keywords: property, marketing mix, purchase decision, service quality, SEM-PLS